Viability of musharakah as an alternative financing mode for small and medium enterprises: The Case of Klang Valley and Selangor, Malaysia - Abdul Razak, Dzuljastri; Mohammed, Mustafa Omar; Abd Rahman, Nur Hasnisda (COMSATS Institute of Information Technology, 2016)
Small and Medium Enterprises ("SMEs") have been recognized as one of the most important component that contributes towards the economic growth of many countries around the world. Despite its importance, SMEs have limited access to external financing that is dominated by debt financing. They have difficulty in fulfilling debt requirements particularly in providing collateral, coping with high interest/ profit payment and adapting to credit rationing. Such limitations curb their growth and expansion.Therefore, there is a need to explore an alternative financing,which is more accessible by SMEs. Quantitative method is adopted in this study. Questionnaires were self administered using drop-off method, to a sample of 100 SMEs firms in Klang Valley and Selangor, Malaysia. The data were analyzed using Exploratory Factor Analysis. Musharakah is found to be s viable alternative financing mode for SMEs. Its three main features, namely (i) risks sharing (ii) profit and loss sharing and (iii) participation have immense potential of salvaging SMEs from their debt based challenges of access to financing, collateral, high interest. This study contributes towards a better understanding of the potential of Musharakah as a viable financing for SMEs. Hence, it provides foundation and direction in structuring Musharakah as an alternative financing mode for SMEs